2019
DOI: 10.1002/admt.201900339
|View full text |Cite
|
Sign up to set email alerts
|

Active Posts in Deterministic Lateral Displacement Devices

Abstract: Using electrically connected metal‐coated posts in a deterministic lateral displacement (DLD) device and applying electric fields, electrokinetics is used to tune separations, significantly decrease the critical size for separation, and increase the dynamic range with switching times on the order of seconds. The strength of DLD stems from its binary behavior. To first approximation, particles move in one out of two trajectories based on their effective size. For particles that are close to the threshold size, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 15 publications
0
25
0
Order By: Relevance
“…Hanasoge et al also used DC field to drive the flow and explore the effect of different array orientations on particle separation in eDLD [ 76 ]. The development of eDLD has been driven primarily by the Tegenfeldt group at Lund University, Sweden, [ 77 , 78 , 79 ] and Morgan group at University of Southampton, UK, [ 39 , 80 , 81 ], who have made use of AC fields in various modes and geometries. Among the benefits of using AC fields are the fact that the flow (carrying the particle through the device) is decoupled from the forces near to the posts (causing separation) and that much greater control can be achieved through the balancing of these forces.…”
Section: Introductionmentioning
confidence: 99%
“…Hanasoge et al also used DC field to drive the flow and explore the effect of different array orientations on particle separation in eDLD [ 76 ]. The development of eDLD has been driven primarily by the Tegenfeldt group at Lund University, Sweden, [ 77 , 78 , 79 ] and Morgan group at University of Southampton, UK, [ 39 , 80 , 81 ], who have made use of AC fields in various modes and geometries. Among the benefits of using AC fields are the fact that the flow (carrying the particle through the device) is decoupled from the forces near to the posts (causing separation) and that much greater control can be achieved through the balancing of these forces.…”
Section: Introductionmentioning
confidence: 99%
“…Beech et al 23 demonstrated that low-frequency AC electric fields applied along the DLD channel in the direction of flow leads to separation of particles smaller than the critical diameter. More recently, the same group reported the use of metal-coated DLD posts to improve this technique 24 , reducing the voltage requirements and the minimum particle size that could be separated at the expense of a more expensive and challenging device fabrication. In a recent publication 25 , we showed how AC electric fields applied orthogonal to the fluid flow can lead to significant and controlled deviation of particles smaller than the critical diameter through the action of a combination of different electrokinetic forces including Electrophoresis (EP) and Dielectrophoresis (DEP).…”
Section: Introductionmentioning
confidence: 99%
“…The device operates using either ac, dc, or a combination of both in order to exploit size, polarizability, and ζ -potential differences between particles. A device by Beech et al [103] uses similar principles but with metalcoated posts.…”
Section: Enrichmentmentioning
confidence: 99%